Prevalence of podoconiosis and its associated factors in Gamo zone, Southern Ethiopia, 2021 - Tamiru Getachew; Chuchu Churko (Journal of Foot and Ankle Research, 2022)
Abstract Background Podoconiosis is a chronic non‐infectious preventable disease. Though not fatal, it may cause social, economic and physical disability. Ethiopia is projected to bear one‐fourth (25%) of the global burden of podoconiosis. Despite its huge economic impact and chronic morbidity and disability, podoconiosis seems to be neglected. Therefore, the aim of this study was to assess the prevalence of podoconiosis and its associated factors in Gamo zone, Southern Ethiopia. Methods A community based cross sectional study was conducted among 683 household members. A multistage sampling method was used to select study participants. Binary logistic regression model was fitted to identify factors associated with podoconiosis. Odds ratio with 95% confidence interval was computed to determine the level of significance; in multivariable analysis, variables with a P value less than 0.05 were considered as statistically significant. Results The prevalence of podoconiosis was 6.2% (95%CI: 4.3–8%). The significantly contributed factors for the prevalence of podoconiosis were wealth index (AOR = 0.249, 95%CI = 0.073–0.845), number of shoes owned (AOR = 6.199, 95% CI = 1.281–29.98), times when individual do not wear shoes (AOR = 2.448, 95%CI = 1.041–5.754), soap utilization during foot washing (AOR = 2.773, 95%CI = 1.210–6.355) and family history of leg swelling (AOR = 4.69, 95%CI = 2.215–9.935). Conclusions This study showed that there was significant burden of podoconiosis in the study area. Wealth index, times when individual do not wear shoes, number of shoes owned, soap utilization during foot washing, and family history of leg swelling were significantly associated with podoconiosis. It is recommended to practice secondary prevention which includes regular foot hygiene and wearing shoes, and the use of antiseptic soaks.